PENGUATAN MINAT BACA DAN KOSA KATA BAHASA INGGRIS MELALUI STORY TELLING PADA ANAK DITAMAN BACA INOVATOR ROBERT FOULTON KOTA SORONG - Sherly Gaspersz; Lulu Jola Uktolseja; Natasya Virginia Leuwol; Melda Agnes Manuhutu (Nindikayla Institute, 2023)
Language is known as a communication tool that can be used by one person or more in spoken or written forms. Efforts to support the presence of language as a means of communication need to be proven with language skills such as: reading, listening, writing, and speaking. One of the problems that exist in the environment of the Robert Fulton Reading Park Km. 9.5 The city of Sorong is still lacking in terms of increasing children's interest in reading and mastering English vocabulary. Therefore, the Community Serving Movement Team (GRAMMAR) is here to provide encouragement and enthusiasm for children through the methods used to try to strengthen children's interest in reading and English vocabulary with the story telling method. This activity begins with the processes of initial observation, permits, implementation of activities, and reports and evaluation of those activities. The results of the activities carried out provide enthusiasm and encouragement for children in an effort to strengthen interest in reading through a commitment to reflection sessions, which are packaged in one unit of these community service activities. It is hoped that the efforts that have been implemented will continue to synergize in efforts to support the national education goal of educating the lives of the nation’s children